THE RELEVANCE OF PATRIOTIC VALUES IN THE NOVEL SANG WARTAWATI CILIK BY GAMAL KOMANDOKO TO NATIONALIST CHARACTER EDUCATION IN ELEMENTARY SCHOOLS - Harnoto; Mukti Widayati; Nurnaningsih (SOSIOEDUKASI, 2026)
Previous studies on patriotic values in literature and the characteristics of nationalism in elementary schools have been conducted separately. This study aims to describe the values of patriotism represented in the novel “Sang Wartawati Cilik” by Gamal Komandoko, the characteristics of nationalism in elementary schools, and the relationship between the two within the context of basic education. This research employed a descriptive qualitative method with a content analysis design using a sociology of literature approach. Data were collected through document study, text analysis, and supporting literature review. Data analysis was conducted using a dialectical approach, while data validity was ensured through source and theory triangulation. The findings reveal that the novel “Sang Wartawati Cilik” by Gamal Komandoko contains patriotic values such as love for the homeland, responsibility, empathy, cooperation, courage, willingness to sacrifice, and perseverance, as reflected through the characters’ actions and the storyline. Nationalism character in elementary schools is developed through habituation and school culture encompassing values of patriotism, responsibility, tolerance, social care, cooperation, politeness, and respect for rights and obligations. The value of patriotism in the novel is relevant to strengthening the character of nationalism in elementary schools, so that children's literature can be used as a means of forming students' character. To ensure these values are internalized optimally, all stakeholders need to collaborate through children’s literary literacy and the habituation of positive attitudes.